Transforming Intensive Arabic Learning Through the TECEP Model and an Inclusive Technology Approach - Laili Mas Ulliyah Hasan; Nada Ibrahim Alribdi (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2026)
This study aims to describe the transformation of Intensive Arabic learning through the TECEP (Tech-Based Eco-Participatory Educational Play Tools) model and an Inclusive Technology approach at State Islamic University of Sunan Ampel (UINSA) Surabaya. The participants were first- and second-semester students from various study programs enrolled in the Intensive Arabic Program (IBA), a compulsory program for new students. The learning process utilized the ALBI (Arabiyyah Linnatiqin Billughoh Indunisiyya) application in digital book (PDF) format and the BARIS ALBI web platform as media for learning materials, exercises, assignments, and examinations. The platform also enabled lecturers to monitor students’ assignment progress and learning outcomes digitally. This study employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings revealed that the implementation of the TECEP model with an Inclusive Technology approach enhanced student participation, created a more interactive and flexible learning environment, and improved learning accessibility for students from diverse academic backgrounds and Arabic proficiency levels. In addition, the digital monitoring system on BARIS ALBI assisted lecturers in effectively tracking students’ learning progress. Therefore, the transformation of Intensive Arabic learning through TECEP and Inclusive Technology represents an innovative learning model that supports the effectiveness and inclusiveness of Arabic learning in Islamic higher education institutions.